Low-carbon concrete additive for lightweight building materials and preparation method thereof

CN122958098APending Publication Date: 2026-10-23MAOMING JUNGUAN NEW MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611323638.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-28
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

但是该专利技术整体组分较为复杂,需要用到改性赤泥与纳米碳化硅来协同提升材料的力学性能,同时也缺乏对抗渗性能的研究

Benefits of technology

[0035](1)本发明低碳混凝土添加剂中絮状木质素纤维作为微米级抗裂保水基体,羧基化纤维素纳米纤维能够实现微裂纹桥接,树枝状二氧化硅接枝改性聚羧酸减水剂属于有机-无机杂化功能助剂,配合聚硅氧烷修饰碳纳米管形成全尺度分级抗裂体系根除裂缝渗水通道,多级孔隙精细化封堵构筑致密防渗基体,水化协同活化提升早强与后期强度,该复合添加剂体系加入到混凝土后,能通过各组分协同实现分散优化、水化活化、多尺度阻裂、多级孔道封堵、界面强化、疏水防渗多重耦合作用,从根本上优化低碳混凝土微观结构,大幅提升抗压力学性能与抗渗耐久性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958098A_ABST
    Figure CN122958098A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of additive materials for light building materials, and particularly relates to a low-carbon concrete additive for light building materials and a preparation method thereof. The preparation method of the low-carbon concrete additive for light building materials comprises the following steps: S1, mixing triethanolamine, cetyltrimethylammonium bromide, sodium salicylate and tetraethyl orthosilicate to prepare dendritic silicon dioxide, and then performing a synthesis reaction on isopentenyl alcohol polyoxyethylene ether, acrylic acid and the dendritic silicon dioxide to obtain a modified water reducing agent; S2, adding the modified water reducing agent and carbon nanotubes into deionized water to obtain a mixture, and then adding a fiber material, bentonite and sodium gluconate for ultrasonic dispersion, and vacuum drying to obtain the low-carbon concrete additive for light building materials. After the additive is added into concrete, the compressive strength can be effectively improved, and a good impermeability grade can be ensured, so that the additive is better applied to light building materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of additives for lightweight building materials, specifically relating to a low-carbon concrete additive for lightweight building materials and its preparation method. Background Technology

[0002] Concrete is an artificial stone material formed by mixing cement, aggregates, water, and admixtures in a reasonable proportion, followed by pouring and hardening. It mainly consists of three core components: cementitious materials, aggregates, and mixing water. Cement, as the core cementitious material, generates a cementitious matrix through hydration, firmly binding coarse and fine aggregates into a whole, giving the concrete structure its integrity. Relying on the dense aggregate structure and the continuous gel system formed after cement hardening, concrete possesses excellent compressive and tensile mechanical properties, while also exhibiting good formability, impermeability, and durability. It is the most widely used core construction material in modern building engineering. Its durability directly determines the service life and structural safety of a building. With the iterative upgrading of building technology, additives have become a key means to optimize concrete performance and improve structural durability.

[0003] Low-carbon concrete additives are a new type of admixture and functional admixture with the core objective of reducing the carbon footprint of concrete throughout its entire life cycle. They can achieve a green and low-carbon upgrade of concrete while ensuring its mechanical and durability properties. Their core characteristics and mechanisms of action are as follows: First, they activate auxiliary cementitious materials, effectively stimulating the potential hydration activity of industrial solid waste admixtures such as fly ash and slag, thereby enhancing their bonding ability. Second, they optimize the cement hydration reaction, improving the cement hydration environment, promoting full and uniform hydration of cement particles, enhancing hydration integrity, and ensuring stable concrete strength and workability. Third, they improve the microstructure, refining the internal pores of concrete and reducing porosity through nanoscale modified components, optimizing the micromechanical properties of the transition zone between aggregates and paste, and significantly improving concrete density, impermeability, and overall durability.

[0004] Chinese patent (publication number CN122059637A) discloses a concrete additive and the concrete thereof. The raw materials, by weight, include modified red mud, wheat straw ash, nano-silicon carbide, graphite, composite fiber, superplasticizer, dipropylene glycol, waterborne polyurethane, high-efficiency water-reducing agent, high-efficiency retarder, and fiber dispersant. The composite fiber is a mixture of loofah fiber, palm fiber, and carbon fiber. This additive is used to prepare high-temperature tunnel lining concrete. Through the synergistic effect of the raw materials, the red mud, nano-silicon carbide, and graphite act as micro-fillers and macro-reinforcers, synergistically improving the mechanical properties and durability of the concrete. However, the overall composition of this patented technology is relatively complex, requiring the use of modified red mud and nano-silicon carbide to synergistically improve the mechanical properties of the material, and it also lacks research on impermeability.

[0005] Therefore, there is an urgent need for a low-carbon concrete additive that, by simplifying the composition and modifying the materials, can significantly improve the compressive strength and impermeability of concrete when added to it, thus enabling its better application in the field of lightweight building materials. Summary of the Invention

[0006] To address the shortcomings of existing technologies, the present invention aims to provide a low-carbon concrete additive for lightweight building materials and its preparation method. The invention involves mixing triethanolamine, hexadecyltrimethylammonium bromide, sodium salicylate, and tetraethyl orthosilicate to obtain dendritic silica. Then, isopentenyl polyoxyethylene ether, acrylic acid, and the dendritic silica are used as raw materials to synthesize a modified water-reducing agent. Next, the modified water-reducing agent and carbon nanotubes are added to deionized water to obtain a mixture. Fiber materials, bentonite, and sodium gluconate are added and ultrasonically dispersed, followed by vacuum drying to obtain the low-carbon concrete additive for lightweight building materials. When added to concrete, the additive of the present invention can effectively improve compressive strength and ensure good impermeability, making it better suited for use in lightweight building materials.

[0007] In a first aspect, the present invention provides a method for preparing a low-carbon concrete additive for lightweight building materials, comprising the following steps:

[0008] S1. A dendritic silica is prepared by mixing triethanolamine, hexadecyltrimethylammonium bromide, sodium salicylate and tetraethyl orthosilicate, and then a modified water-reducing agent is obtained by using isopentenyl polyoxyethylene ether, acrylic acid and the dendritic silica as raw materials for synthesis reaction.

[0009] S2. Add the modified water-reducing agent and carbon nanotubes to deionized water to obtain a mixture, then add fiber materials, bentonite and sodium gluconate, ultrasonically disperse, and vacuum dry to obtain a low-carbon concrete additive for lightweight building materials.

[0010] As a preferred technical solution of the present invention, the conditions for ultrasonic dispersion in step S2 are: ultrasonic power of 600~700W and ultrasonic dispersion time of 6~8min.

[0011] As a preferred technical solution of the present invention, the components in step S2 include, by weight, 50-60 parts of modified water-reducing agent, 15-25 parts of carbon nanotubes, 80-90 parts of deionized water, 20-30 parts of fiber material, 10-20 parts of bentonite, and 10-20 parts of sodium gluconate.

[0012] As a preferred technical solution of the present invention, the modified water-reducing agent may be in the following weight proportions: 50 parts, 52 parts, 54 parts, 56 parts, 58 parts, or 60 parts, etc.

[0013] As a preferred embodiment of the present invention, the carbon nanotubes may be in the following weight proportions: 15 parts, 17 parts, 19 parts, 21 parts, 23 parts, or 25 parts, etc.

[0014] As a preferred embodiment of the present invention, the weight parts of the fiber material may be 20 parts, 22 parts, 24 parts, 26 parts, 28 parts, or 30 parts, etc.

[0015] As a preferred embodiment of the present invention, the weight parts of the bentonite can be 10 parts, 12 parts, 14 parts, 16 parts, 18 parts or 20 parts, etc.

[0016] As a preferred embodiment of the present invention, the sodium gluconate may be in the following weight proportions: 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, or 20 parts, etc.

[0017] As a preferred technical solution of the present invention, the preparation steps of the dendritic silica are as follows: by weight, 2-4 parts of triethanolamine are added to 150-200 parts of deionized water, and stirred at 75-80°C for 30-40 minutes. Then, 1-3 parts of hexadecyltrimethylammonium bromide are added and stirred for 60-80 minutes. Then, 0.1-0.3 parts of sodium salicylate are added and stirred for 2-4 hours. Finally, 15-25 parts of tetraethyl orthosilicate are added dropwise and stirred for 20-30 minutes. After centrifugation, the precipitate is washed with anhydrous ethanol to obtain dendritic silica.

[0018] As a preferred embodiment of the present invention, the steps of the synthesis reaction are as follows: by weight, 20-25 parts of the dendritic silica are dispersed in 180-200 parts of deionized water to form a suspension; 20-30 parts of acrylic acid and 90-100 parts of deionized water are mixed to obtain solution A; 0.6-0.8 parts of 3-mercaptopropionic acid and 0.6-0.8 parts of ascorbic acid are added to 10-20 parts of deionized water and stirred to obtain solution B; 240-250 parts of isopentenyl alcohol polyoxyethylene ether and 800-900 parts of deionized water are mixed and stirred at 50-60°C for 60-80 minutes; then 15-20 parts of 30% hydrogen peroxide solution are added to obtain a mixed solution; then solution A, solution B and suspension are added dropwise and the synthesis reaction is carried out at 35-40°C for 2-4 hours; the mixture is cooled to room temperature, filtered, washed with water, and dried to obtain the modified water-reducing agent.

[0019] This invention first uses tetraethyl orthosilicate as the main raw material and employs the classic sol-gel method to synthesize nano-silica with a dendritic structure through template agent guidance. Then, isopentenyl polyoxyethylene ether provides long polyether side chains, acrylic acid provides carboxyl groups, and 3-mercaptopropionic acid is used as a chain transfer agent for in-situ polymerization. The silanol groups on the surface of the dendritic silica undergo esterification with the carboxyl groups in the water-reducing agent molecule, grafting the nanoparticles onto the main chain of the polycarboxylate water-reducing agent molecule, thereby obtaining a polycarboxylate water-reducing agent grafted with dendritic silica.

[0020] As a preferred embodiment of the present invention, the carbon nanotubes are polysiloxane-modified carbon nanotubes.

[0021] As a preferred technical solution of the present invention, the preparation method of the polysiloxane-modified carbon nanotubes is as follows: first, hyperbranched polysiloxane is prepared using 3-aminopropyltriethoxysilane as a raw material, and then the surface of carbon nanotube powder is modified using the hyperbranched polysiloxane to obtain polysiloxane-modified carbon nanotubes.

[0022] As a preferred technical solution of the present invention, the preparation steps of the hyperbranched polysiloxane are as follows: by weight, 80-90 parts of 3-aminopropyltriethoxysilane are added to 140-160 parts of deionized water and mixed evenly. The pH is adjusted to 4.5-5.0 with hydrochloric acid solution and the temperature is raised to 50-55°C for 3-4 hours. After the reaction is completed, the mixture is rotary evaporated and vacuum dried to obtain the hyperbranched polysiloxane.

[0023] As a preferred embodiment of the present invention, the surface modification treatment steps are as follows: by weight, 400-450 parts of anhydrous ethanol and 50-100 parts of deionized water are mixed in a reaction vessel, then 0.04-0.06 parts of sodium dodecylbenzenesulfonate and 2-4 parts of carbon nanotube powder are added and ultrasonically dispersed for 30-40 minutes, then 10-12 parts of hyperbranched polysiloxane and 0.6-0.8 parts of dibutyltin dilaurate are added and stirred for reaction. After the reaction is completed, the mixture is filtered, and the filter residue is washed with acetone and anhydrous ethanol in sequence, and then vacuum dried to obtain polysiloxane-modified carbon nanotubes.

[0024] As a preferred embodiment of the present invention, the conditions for the stirring reaction are: stirring speed of 300~350 r / min, reaction temperature of 85~90℃, and reaction time of 24~30 h.

[0025] As a preferred embodiment of the present invention, the carbon nanotube powder is a fluorinated carbon nanotube powder with a surface partially fluorinated, a fluorine content of 40~60wt%, an outer diameter of 10~50nm, and a length of 1~10μm.

[0026] This invention first uses 3-aminopropyltriethoxysilane as a raw material, and generates a Si-O-Si branched structure through hydrochloric acid-catalyzed intermolecular dehydration condensation of silanol molecules, forming a hyperbranched polysiloxane with multiple hydroxyl groups and amino groups on the side chains. A large number of active silanol groups are retained on the periphery of the molecule, providing reaction sites for subsequent grafting with carbon nanotubes. Subsequently, the hyperbranched polysiloxane is mixed with fluorinated carbon nanotubes with partially fluorinated surfaces, and under the action of dibutyltin laurate catalyst, the silanol groups of the former and the residual hydroxyl groups on the surface of the latter undergo dehydration condensation to form stable covalent bonds, finally obtaining polysiloxane-modified carbon nanotubes.

[0027] As a preferred embodiment of the present invention, the fiber material is selected from one or more of cellulose nanofibers, polypropylene fibers, basalt fibers, carbon fibers, glass fibers, and lignin fibers.

[0028] As a preferred embodiment of the present invention, the fiber material is cellulose nanofiber and lignin fiber.

[0029] As a preferred embodiment of the present invention, the mass ratio of cellulose nanofibers to lignin fibers in the fiber material is (1~2):1.

[0030] As a preferred embodiment of the present invention, the cellulose nanofibers are carboxylated cellulose nanofibers.

[0031] As a preferred embodiment of the present invention, the lignin fiber is a flocculent lignin fiber with an average length of 2-5 mm, an ash content of 10-25%, a pH value of 6.5-8.5, and a moisture content of 2-5%.

[0032] The fiber material of the present invention can use cellulose nanofibers, polypropylene fibers, basalt fibers, carbon fibers, glass fibers, lignin fibers, with carboxylated cellulose nanofibers and flocculent lignin fibers being preferred for compounding. By controlling the mass ratio of the two and adding them to low-carbon concrete additives, a good compounding effect is achieved, effectively improving the comprehensive performance of concrete.

[0033] A second aspect of the present invention provides a low-carbon concrete additive for lightweight building materials prepared by the preparation method described in the first aspect.

[0034] Compared with the prior art, the beneficial effects of the present invention are:

[0035] (1) In the low-carbon concrete additive of the present invention, flocculent lignin fiber serves as a micron-level crack-resistant and water-retaining matrix, carboxylated cellulose nanofibers can achieve microcrack bridging, and dendritic silica grafted modified polycarboxylate superplasticizer is an organic-inorganic hybrid functional additive. Combined with polysiloxane modified carbon nanotubes, it forms a full-scale graded crack-resistant system to eliminate crack seepage channels, and multi-level pore fine sealing constructs a dense impermeable matrix. Hydration synergistic activation enhances early strength and later strength. After this composite additive system is added to concrete, it can achieve multiple coupling effects of dispersion optimization, hydration activation, multi-scale crack resistance, multi-level pore sealing, interface strengthening, and hydrophobic seepage prevention through the synergistic effect of each component. It fundamentally optimizes the microstructure of low-carbon concrete and greatly improves its compressive mechanical properties and impermeability durability.

[0036] (2) The dendritic silica grafted onto the water-reducing agent in the additive of the present invention has a large specific surface area, which can be used as a "nucleus" for cement hydration to accelerate the hydration reaction. Combined with nano silica with a dendritic structure, it can better fill the micropores in the cement matrix and directly improve the compressive strength of concrete by making the internal structure more compact. On the other hand, the carboxyl groups and silanol groups on the modified polycarboxylate water-reducing agent can be strongly adsorbed on the surface of cement particles through chemical bonding. By forming a dense and firm adsorption layer and interfacial bonding, the penetration path is blocked. Meanwhile, the dendritic silica effectively fills the interfacial transition zone and cuts off the transmission channel of harmful media. The combined effect improves the impermeability grade of the material.

[0037] (3) The polysiloxane-modified carbon nanotubes in the additive of the present invention can fill the capillary pores, gel pores and micropores in the interface transition zone generated by cement hydration. The hyperbranched siloxane hydrophobic branches fill the inner wall of the pores to further reduce the stress concentration inside the pores. At the same time, the modified fluorinated carbon nanotubes are uniformly dispersed in the cement matrix to form a three-dimensional nano-reinforcing network that penetrates the interior, thereby effectively improving the compressive strength of concrete. On the other hand, the polysiloxane-modified carbon nanotubes can fill the pores at all levels to cut off the penetration channels of corrosive ions. The fluorine element of the fluorinated carbon nanotubes and the hyperbranched polysiloxane hydrophobic siloxane branches together construct a fluorosilicone hydrophobic layer, reduce the surface energy of the pore wall and form a hydrophobic interface. Fluorine and silicon synergistically enhance the impermeability of concrete.

[0038] (4) The carboxylated cellulose nanofibers in the additive of this invention can refine the pores and densify the matrix at the microscopic level, while the flocculent lignin fibers can block cracks and reduce water seepage channels at the macroscopic level. The combination of the two can greatly reduce the permeability of concrete and thus significantly improve the impermeability grade. In addition, the carboxylation modification of cellulose nanofibers improves the chemical compatibility and bonding force between the fiber and the cement matrix, and can effectively strengthen the interface transition zone between aggregate and cement paste. The lignin fibers can improve the toughness and integrity of concrete and prevent brittle failure by blocking cracks and dispersing stress. The synergistic effect enables the concrete to resist the destruction of the internal microstructure and inhibit the penetration of macroscopic cracks when subjected to pressure, ultimately improving the compressive strength of the concrete. Attached Figure Description

[0039] Figure 1 The image shows the FTIR spectra of the modified water-reducing agent and dendritic silica in Example 1.

[0040] Figure 2 This is a microscopic morphology diagram of the modified water-reducing agent in Example 1.

[0041] Figure 3 The images show the FTIR spectra of polysiloxane-modified carbon nanotubes and fluorinated carbon nanotubes in Example 1.

[0042] Figure 4 XPS images of polysiloxane-modified carbon nanotubes and fluorinated carbon nanotubes in Example 1. Detailed Implementation

[0043] To facilitate understanding of the present invention, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be construed as limiting the scope of the invention.

[0044] The sources of some components in the examples and comparative examples are as follows:

[0045] Commercially available polycarboxylate superplasticizer, model JF-HP, purchased from Shandong Liangzheng New Material Technology Co., Ltd.

[0046] Triethanolamine, CAS No. 102-71-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.

[0047] Hexadecyltrimethylammonium bromide, CAS No. 57-09-0, was purchased from Shanghai Maclean Biochemical Technology Co., Ltd.

[0048] Sodium salicylate, CAS No. 54-21-7, was purchased from Shanghai Maclean Biochemical Technology Co., Ltd.

[0049] Tetraethyl orthosilicate, CAS No. 78-10-4, purchased from Sinopharm Chemical Reagent Co., Ltd.

[0050] Isoprene alcohol polyoxyethylene ether, model TPEG-2400, was purchased from Jilin Zhongxin Chemical Co., Ltd.

[0051] Acrylic acid, CAS No. 79-10-7, purchased from Sinopharm Chemical Reagent Co., Ltd.

[0052] 3-Mercaptopropionic acid, CAS No. 107-96-0, was purchased from Shanghai Maclean Biochemical Technology Co., Ltd.

[0053] Ascorbic acid, CAS No. 50-81-7, purchased from Sinopharm Chemical Reagent Co., Ltd.

[0054] Hydrogen peroxide solution, catalog number H112515, mass fraction 30%, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0055] Fluorinated carbon nanotube powder, item number 101909, with partial fluorination on the surface, fluorine content of 50wt%, outer diameter of 25nm, and length of 5μm, was purchased from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd.

[0056] Multi-walled carbon nanotube powder, item number 100229, purchased from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd.

[0057] 3-Aminopropyltriethoxysilane, CAS No. 919-30-2, was purchased from Shanghai Maclean Biochemical Technology Co., Ltd.

[0058] Sodium dodecylbenzenesulfonate, CAS No. 25155-30-0, was purchased from Sinopharm Chemical Reagent Co., Ltd.

[0059] Dibutyltin dilaurate, CAS No. 77-58-7, purchased from Sinopharm Chemical Reagent Co., Ltd.

[0060] Basalt fiber, product number FD2706, was purchased from Shandong Oude Chemical Fiber Products Co., Ltd.

[0061] Carboxylated cellulose nanofibers, model J6423CP, purchased from Seruna Technology Co., Ltd.

[0062] Flocculent lignin fiber, model JW, with an average length of 4.5 mm, ash content of 15.5%, pH value of 7.2, and moisture content of 4.4%, was purchased from Jiangsu Wenchang New Material Technology Co., Ltd.

[0063] Bentonite, item number N431707, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0064] Sodium gluconate, CAS No. 527-07-1, was purchased from Shanghai Maclean Biochemical Technology Co., Ltd.

[0065] Example 1

[0066] This embodiment provides a method for preparing a low-carbon concrete additive for lightweight building materials, including the following steps:

[0067] S1. By weight, add 4 parts of triethanolamine to 200 parts of deionized water and stir at 80°C for 30 min. Then add 3 parts of hexadecyltrimethylammonium bromide and stir for 80 min. Next, add 0.3 parts of sodium salicylate and stir for 4 h. Finally, add 25 parts of tetraethyl orthosilicate and stir for 30 min. Centrifuge and wash the precipitate with anhydrous ethanol to obtain dendritic silica. Disperse 25 parts of the dendritic silica in 200 parts of deionized water to form a suspension. Mix 30 parts of acrylic acid and 100 parts of deionized water to obtain solution A. Add 0.8 parts of 3... Mercaptopropionic acid and 0.8 parts ascorbic acid were added to 20 parts deionized water and stirred to obtain solution B. 250 parts isopentenyl alcohol polyoxyethylene ether and 900 parts deionized water were mixed and stirred at 60°C for 60 min. Then, 20 parts of 30% hydrogen peroxide solution were added to obtain a mixed solution. Next, solutions A, B, and the suspension were added dropwise, and the synthesis reaction was carried out at 40°C for 2 h. After cooling to room temperature, the mixture was filtered, washed with water, and dried to obtain the modified water-reducing agent. The properties of the related materials were characterized, and the infrared spectra of the modified water-reducing agent and dendritic silica are shown below. Figure 1 As shown, the microstructure of the modified water-reducing agent is as follows: Figure 2 As shown.

[0068] S2. Add 60 parts of modified water-reducing agent and 25 parts of carbon nanotubes to 90 parts of deionized water to obtain a mixture. Then add 30 parts of basalt fiber (item number FD2706), 20 parts of bentonite and 20 parts of sodium gluconate and ultrasonically disperse at 700W for 6 minutes. Vacuum dry to obtain a low-carbon concrete additive for lightweight building materials.

[0069] Preparation of polysiloxane-modified carbon nanotubes: 90 parts by weight of 3-aminopropyltriethoxysilane were added to 160 parts by weight of deionized water and mixed thoroughly. The pH was adjusted to 5.0 with hydrochloric acid solution, and the mixture was heated to 55°C and reacted for 3 hours. After the reaction, the mixture was rotary evaporated and vacuum dried to obtain hyperbranched polysiloxane. 450 parts by weight of anhydrous ethanol and 50 parts by weight of deionized water were mixed in a reaction vessel. Then, 0.06 parts by weight of sodium dodecylbenzenesulfonate and 4 parts by weight of fluorinated carbon nanotube powder were added and ultrasonically dispersed for 40 minutes. Next, 12 parts by weight of hyperbranched polysiloxane and 0.8 parts by weight of dibutyltin dilaurate were added and stirred at 350 r / min. The reaction temperature was 90°C, and the reaction time was 24 hours. After the reaction, the mixture was filtered, and the filter residue was washed successively with acetone and anhydrous ethanol, and then vacuum dried to obtain polysiloxane-modified carbon nanotubes. The properties of the materials were characterized. The infrared spectra of the polysiloxane-modified carbon nanotubes and fluorinated carbon nanotubes are shown below. Figure 3As shown, the X-ray photoelectron spectra of polysiloxane-modified carbon nanotubes and fluorinated carbon nanotubes are as follows: Figure 4 As shown.

[0070] Example 2

[0071] This embodiment provides a method for preparing a low-carbon concrete additive for lightweight building materials, including the following steps:

[0072] S1. By weight, add 2 parts of triethanolamine to 150 parts of deionized water and stir at 75°C for 40 min. Then add 1 part of hexadecyltrimethylammonium bromide and stir for 60 min. Next, add 0.1 parts of sodium salicylate and stir for 2 h. Finally, add 15 parts of tetraethyl orthosilicate and stir for 20 min. Centrifuge and wash the precipitate with anhydrous ethanol to obtain dendritic silica. Disperse 20 parts of the dendritic silica in 180 parts of deionized water to form a suspension. Add 20 parts of acrylic acid and 90 parts of deionized water... Solution A was obtained by mixing with deionized water. 0.6 parts of 3-mercaptopropionic acid and 0.6 parts of ascorbic acid were added to 10 parts of deionized water and stirred to obtain solution B. 240 parts of isopentenyl alcohol polyoxyethylene ether and 800 parts of deionized water were mixed and stirred at 50°C for 80 min. Then, 15 parts of 30% hydrogen peroxide solution were added to obtain a mixed solution. Solution A, solution B and suspension were then added dropwise and the synthesis reaction was carried out at 35°C for 4 h. After cooling to room temperature, the solution was filtered, washed with water and dried to obtain the modified water-reducing agent.

[0073] S2. Add 50 parts of modified water-reducing agent and 15 parts of carbon nanotubes to 80 parts of deionized water to obtain a mixture. Then add 20 parts of carboxylated cellulose nanofibers, 10 parts of bentonite and 10 parts of sodium gluconate and ultrasonically disperse at 600W for 8 minutes. Vacuum dry to obtain a low-carbon concrete additive for lightweight building materials.

[0074] Preparation of polysiloxane-modified carbon nanotubes: 80 parts by weight of 3-aminopropyltriethoxysilane were added to 140 parts of deionized water and mixed evenly. The pH was adjusted to 4.5 with hydrochloric acid solution and the temperature was raised to 50℃ for 4 hours. After the reaction, the mixture was rotary evaporated and vacuum dried to obtain hyperbranched polysiloxane. 400 parts of anhydrous ethanol and 100 parts of deionized water were mixed evenly in a reaction vessel. Then, 0.04 parts of sodium dodecylbenzenesulfonate and 2 parts of fluorinated carbon nanotube powder were added and ultrasonically dispersed for 30 minutes. Then, 10 parts of hyperbranched polysiloxane and 0.6 parts of dibutyltin dilaurate were added and stirred for reaction at a stirring speed of 300 r / min, a reaction temperature of 85℃, and a reaction time of 230 hours. After the reaction, the mixture was filtered. The filter residue was washed with acetone and anhydrous ethanol in sequence and vacuum dried to obtain polysiloxane-modified carbon nanotubes.

[0075] Example 3

[0076] This embodiment provides a method for preparing a low-carbon concrete additive for lightweight building materials, including the following steps:

[0077] S1. By weight, add 3 parts of triethanolamine to 180 parts of deionized water and stir at 78°C for 34 min. Then add 2 parts of hexadecyltrimethylammonium bromide and stir for 70 min. Next, add 0.3 parts of sodium salicylate and stir for 3 h. Finally, add 18 parts of tetraethyl orthosilicate and stir for 24 min. Centrifuge and wash the precipitate with anhydrous ethanol to obtain dendritic silica. Disperse 22 parts of the dendritic silica in 190 parts of deionized water to form a suspension. Add 26 parts of acrylic acid and 98 parts of deionized water... Solution A was obtained by mixing with deionized water. 0.7 parts of 3-mercaptopropionic acid and 0.7 parts of ascorbic acid were added to 14 parts of deionized water and stirred to obtain solution B. 245 parts of isopentenyl alcohol polyoxyethylene ether and 850 parts of deionized water were mixed and stirred at 54°C for 70 min. Then, 18 parts of 30% hydrogen peroxide solution were added to obtain a mixed solution. Solution A, solution B and suspension were then added dropwise and the synthesis reaction was carried out at 36°C for 3 h. After cooling to room temperature, the solution was filtered, washed with water and dried to obtain the modified water-reducing agent.

[0078] S2. Add 56 parts of modified water-reducing agent and 18 parts of carbon nanotubes to 85 parts of deionized water to obtain a mixture. Then add 25 parts of flocculent lignin fiber, 16 parts of bentonite and 14 parts of sodium gluconate and ultrasonically disperse at 650W for 7 minutes. Vacuum dry to obtain a low-carbon concrete additive for lightweight building materials.

[0079] Preparation of polysiloxane-modified carbon nanotubes: 85 parts by weight of 3-aminopropyltriethoxysilane were added to 150 parts of deionized water and mixed evenly. The pH was adjusted to 4.8 with hydrochloric acid solution and the temperature was raised to 52℃ for 3.5 h. After the reaction, the mixture was rotary evaporated and vacuum dried to obtain hyperbranched polysiloxane. 420 parts of anhydrous ethanol and 80 parts of deionized water were mixed evenly in a reaction vessel. Then, 0.05 parts of sodium dodecylbenzenesulfonate and 3 parts of fluorinated carbon nanotube powder were added and ultrasonically dispersed for 35 min. Then, 11 parts of hyperbranched polysiloxane and 0.7 parts of dibutyltin dilaurate were added and stirred for reaction. The stirring speed was 320 r / min, the reaction temperature was 88℃, and the reaction time was 26 h. After the reaction, the mixture was filtered. The filter residue was washed with acetone and anhydrous ethanol in sequence and vacuum dried to obtain polysiloxane-modified carbon nanotubes.

[0080] Example 4

[0081] The difference between this embodiment and Embodiment 1 is that the fiber material is changed to 20 parts of carboxylated cellulose nanofibers and 10 parts of flocculent lignin fiber.

[0082] Example 5

[0083] The difference between this embodiment and Embodiment 1 is that the fiber material is changed to 25 parts of carboxylated cellulose nanofibers and 5 parts of flocculent lignin fibers.

[0084] Example 6

[0085] The difference between this embodiment and Embodiment 1 is that the fiber material is changed to 5 parts carboxylated cellulose nanofibers and 25 parts flocculent lignin fibers.

[0086] Comparative Example 1

[0087] The difference between this comparative example and Example 1 is that a commercially available polycarboxylate superplasticizer (model JF-HP) was used instead of the modified superplasticizer.

[0088] Comparative Example 2

[0089] The difference between this comparative example and Example 1 is that nano-silica (item number S490064) was used instead of dendritic silica in the preparation of the modified water-reducing agent.

[0090] Comparative Example 3

[0091] The difference between this comparative example and Example 1 is that fluorinated carbon nanotube powder (item number 101909) was used instead of polysiloxane-modified carbon nanotubes.

[0092] Comparative Example 4

[0093] The difference between this comparative example and Example 1 is that multi-walled carbon nanotube powder (item number 100229) was used instead of fluorinated carbon nanotube powder (item number 101909) in the preparation of polysiloxane-modified carbon nanotubes.

[0094] Performance testing

[0095] The concrete composition includes: 200 parts cement, 150 parts water, 200 parts silica fume, 1000 parts silica sand, and 30 parts additives from the examples or comparative examples; the concrete performance was tested as follows:

[0096] (1) Slump: The test shall be conducted in accordance with the requirements of GB / T 50080-2016 Standard for Test Methods of Performance of Ordinary Concrete Mixtures.

[0097] (2) Compressive strength: The test shall be conducted in accordance with the requirements of GB / T 50081-2019 Standard for Test Methods of Physical and Mechanical Properties of Concrete.

[0098] (3) Permeability grade: The test shall be conducted in accordance with the requirements of GB / T 50082-2024 Standard for Test Methods of Long-term Performance and Durability of Concrete.

[0099] The performance test data above are shown in Table 1.

[0100] Table 1 Performance Test Results

[0101]

[0102] As can be seen from the above, the present invention prepares dendritic silica by mixing triethanolamine, hexadecyltrimethylammonium bromide, sodium salicylate and tetraethyl orthosilicate, and then uses isopentenyl polyoxyethylene ether, acrylic acid and the dendritic silica as raw materials to carry out a synthesis reaction to obtain a modified water-reducing agent. Next, the modified water-reducing agent and carbon nanotubes are added to deionized water to obtain a mixture. Fiber materials, bentonite and sodium gluconate are added and ultrasonically dispersed, and vacuum dried to obtain a low-carbon concrete additive for lightweight building materials.

[0103] Compared with Example 1, the fiber material was changed to 20 parts of carboxylated cellulose nanofibers and 10 parts of flocculent lignin fibers. Since the combination of carboxylated cellulose nanofibers and flocculent lignin fibers achieved a good synergistic effect, the compressive strength of the material increased and the impermeability was improved after the additive was added to the concrete (Example 4).

[0104] Compared with Example 4, the fiber material was changed to 25 parts of carboxylated cellulose nanofiber and 5 parts of flocculent lignin fiber. Due to the excessive amount of carboxylated cellulose nanofiber, the compounding effect was not good. Therefore, the compressive strength of the material was reduced and the impermeability was reduced after the additive was added to the concrete (Example 5).

[0105] Compared with Example 4, the fiber material was changed to 5 parts of carboxylated cellulose nanofiber and 25 parts of flocculent lignin fiber. Due to the excessive amount of flocculent lignin fiber, the compounding effect was not good. Therefore, the compressive strength of the material was reduced and the impermeability was reduced after the additive was added to the concrete (Example 6).

[0106] Compared with Example 1, the use of commercially available polycarboxylate superplasticizer (model JF-HP) instead of modified superplasticizer resulted in poor performance due to the lack of the modified superplasticizer. Consequently, the compressive strength of the material decreased and the impermeability was reduced after the additive was added to the concrete (Comparative Example 1).

[0107] Compared with Example 1, the use of nano silica (item number S490064) to replace dendritic silica in the preparation of modified water-reducing agent resulted in poor performance due to the lack of dendritic silica. Consequently, the compressive strength of the material decreased and the impermeability was reduced after the additive was added to the concrete (Comparative Example 2).

[0108] Compared with Example 1, fluorinated carbon nanotube powder (item number 101909) was used to replace polysiloxane to modify carbon nanotubes. The lack of polysiloxane modification resulted in poor performance, and the compressive strength and impermeability of the material were reduced after the additive was added to the concrete (Comparative Example 3).

[0109] Compared with Example 1, multi-walled carbon nanotube powder (item number 100229) was used to replace fluorinated carbon nanotube powder (item number 101909) in the preparation of polysiloxane modified carbon nanotubes. The lack of the effect of fluorinated carbon nanotube powder resulted in poor performance. As a result, the compressive strength of the material was reduced and the impermeability was decreased after the additive was added to the concrete (Comparative Example 4).

Claims

1. A method for preparing a low-carbon concrete additive for lightweight building materials, characterized in that, Includes the following steps: S1. A dendritic silica is prepared by mixing triethanolamine, hexadecyltrimethylammonium bromide, sodium salicylate and tetraethyl orthosilicate, and then a modified water-reducing agent is obtained by using isopentenyl polyoxyethylene ether, acrylic acid and the dendritic silica as raw materials for synthesis reaction. S2. Add the modified water-reducing agent and carbon nanotubes to deionized water to obtain a mixture, then add fiber materials, bentonite and sodium gluconate, ultrasonically disperse, and vacuum dry to obtain a low-carbon concrete additive for lightweight building materials.

2. The method for preparing a low-carbon concrete additive for lightweight building materials according to claim 1, characterized in that, The components in step S2, by weight, include: 50-60 parts modified water-reducing agent, 15-25 parts carbon nanotubes, 80-90 parts deionized water, 20-30 parts fiber material, 10-20 parts bentonite, and 10-20 parts sodium gluconate.

3. The method for preparing a low-carbon concrete additive for lightweight building materials according to claim 1, characterized in that, The preparation steps of the dendritic silica are as follows: by weight, 2-4 parts of triethanolamine are added to 150-200 parts of deionized water and stirred at 75-80°C for 30-40 minutes. Then, 1-3 parts of hexadecyltrimethylammonium bromide are added and stirred for 60-80 minutes. Next, 0.1-0.3 parts of sodium salicylate are added and stirred for 2-4 hours. Finally, 15-25 parts of tetraethyl orthosilicate are added dropwise and stirred for 20-30 minutes. After centrifugation, the precipitate is washed with anhydrous ethanol to obtain dendritic silica.

4. The method for preparing a low-carbon concrete additive for lightweight building materials according to claim 1, characterized in that, The steps of the synthesis reaction are as follows: 20-25 parts by weight of the dendritic silica are dispersed in 180-200 parts of deionized water to form a suspension; 20-30 parts by weight of acrylic acid and 90-100 parts by weight of deionized water are mixed to obtain solution A; 0.6-0.8 parts by weight of 3-mercaptopropionic acid and 0.6-0.8 parts by weight of ascorbic acid are added to 10-20 parts by weight of deionized water and stirred to obtain solution B; 240-250 parts by weight of isopentenyl alcohol polyoxyethylene ether and 800-900 parts by weight of deionized water are mixed and stirred at 50-60°C for 60-80 min; then 15-20 parts by weight of 30% hydrogen peroxide solution are added to obtain a mixed solution; then solutions A, B and the suspension are added dropwise and the synthesis reaction is carried out at 35-40°C for 2-4 h; the mixture is cooled to room temperature, filtered, washed with water, and dried to obtain the modified water-reducing agent.

5. The method for preparing a low-carbon concrete additive for lightweight building materials according to claim 1, characterized in that, The carbon nanotubes are polysiloxane-modified carbon nanotubes. The preparation method of the polysiloxane-modified carbon nanotubes is as follows: first, hyperbranched polysiloxane is prepared using 3-aminopropyltriethoxysilane as a raw material, and then the surface of carbon nanotube powder is modified using the hyperbranched polysiloxane to obtain polysiloxane-modified carbon nanotubes.

6. The method for preparing a low-carbon concrete additive for lightweight building materials according to claim 5, characterized in that, The preparation steps of the hyperbranched polysiloxane are as follows: by weight, 80-90 parts of 3-aminopropyltriethoxysilane are added to 140-160 parts of deionized water and mixed evenly. The pH is adjusted to 4.5-5.0 with hydrochloric acid solution and the temperature is raised to 50-55℃ for 3-4 hours. After the reaction is completed, the mixture is rotary evaporated and vacuum dried to obtain the hyperbranched polysiloxane.

7. The method for preparing a low-carbon concrete additive for lightweight building materials according to claim 5, characterized in that, The surface modification process is as follows: 400-450 parts by weight of anhydrous ethanol and 50-100 parts by weight of deionized water are mixed in a reaction vessel, then 0.04-0.06 parts by weight of sodium dodecylbenzenesulfonate and 2-4 parts by weight of carbon nanotube powder are added and ultrasonically dispersed for 30-40 minutes. Then 10-12 parts by weight of hyperbranched polysiloxane and 0.6-0.8 parts by weight of dibutyltin dilaurate are added and stirred for reaction. After the reaction is completed, the mixture is filtered, and the filter residue is washed with acetone and anhydrous ethanol in sequence and vacuum dried to obtain polysiloxane-modified carbon nanotubes.

8. The method for preparing a low-carbon concrete additive for lightweight building materials according to claim 1, characterized in that, The fiber material is selected from one or more of cellulose nanofibers, polypropylene fibers, basalt fibers, carbon fibers, glass fibers, and lignin fibers.

9. The method for preparing a low-carbon concrete additive for lightweight building materials according to claim 8, characterized in that, The fiber material is cellulose nanofiber and lignin fiber; The mass ratio of cellulose nanofibers to lignin fibers in the fiber material is (1~2):

1.

10. A low-carbon concrete additive for lightweight building materials, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Concrete additive and concrete thereof

    CN122059637A